Preliminary In Vitro Assessment of Effects of Leaf Extracts of Various Sansevieria Thunb. Species on the Lipid Peroxidation Level in the Equine Plasma - Tkachenko, Halina; Buyun, Lyudmyla; Kurhaluk, Natalia; Maryniuk, Myroslava; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The aim of this study was to evaluate the in vitro effect of buffer extracts obtained from the leaves of various Sansevieria species against lipid peroxidation in the equine plasma. The succulent leaves of living plants of Sansevieria francisii Chahin, S. caulescens N.E.Br., S. suffruticosa N.E.Br., S. roxburghiana Schult. & Schult.f., S. metallica Gérôme & Labroy, S. gracilis N.E.Br., S. hyacinthoides (L.) Druce, S. cylindrica Bojer ex Hook., S. canaliculata Carrière, S. aethiopica Thunb., S. kirkii Baker, S. trifasciata Prain, S. forskaliana (Schult. & Schult.f.) Hepper & J.R.I. Wood, S. fischeri (Baker) Marais, S. dooneri N.E.Br., S. intermedia N.E.Br., S. parva N.E.Br. were sampled for the study. Freshly collected leaves were washed, weighed, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in proportion 1:19, w/w) at room temperature. The extracts were then filtered and investigated for their pro-oxidant and antioxidant activity. A volume of 0.1 mL of the various extracts was incubated with 1.9 mL of equine plasma at 37 °C for 60 min with continuous stirring. The results of the study showed that the TBARS level as a biomarker of lipid peroxidation was significantly increased after incubation with extracts of selected species belonging to the Sansevieria genus and these results were statistically significant. The most potent effect was demonstrated by the S. intermedia, S. forskaliana, S. trifasciata, S. parva, and S. caulescens leaf extracts compared to phosphate buffer as control sample (increased by 65.6, 53.2, 51.6, 50, and 48 %, respectively). S. kirkii, S. aethiopica, and S. suffruticosa caused the less increase of the TBARS level after 1-h incubation with equine plasma (by 18.8, 27.6, and 30.8 %, respectively, p<0.05). To conclude, Sansevieria species possess a promising antioxidant and pro-oxidant potential. Further studies involving phytochemical identification of the main compounds in plants are necessary to affirm and maximize the possible use of the plants as a therapeutic remedy for the prevention of oxidative stress. The dose-depended antioxidative and pro-oxidative effects of various Sansevieria species in both plasma and erythrocyte suspension will be further studied in detail.